Police, Power, and the Production of Racial Boundaries - Muñiz, Ana, 1984- (Book collections on Project MUSE., 2015)
Based on five years of ethnography, archival research, census data analysis, and interviews, Police, Power, and the Production of Racial Boundaries reveals how the LAPD, city prosecutors, and business owners struggled to control who should be considered "dangerous" and how they should be policed in Los Angeles. Ana Mu#65533;iz shows how this influential group used policies and everyday procedures to criminalize behaviors commonly associated with blacks and Latinos and to promote an exceedingly aggressive form of policing.